Pengaruh Model Prediksi Kebangkrutan, Leverage, Audit Lag, Dan Ukuran Perusahaan Terhadap Opini Audit Going Concern - Salean, Anastasia Paula (Ultimaccounting Jurnal Ilmu Akuntansi, 2013)
The objective of this research is to examine the effect of bankruptcy prediction model, leverage, audit lag, and company size towards obtaining a going concern audit opinion. The samples in this study are 11 companies listed in Indonesian Stock Exchange being classified as manufacturing sector in the year 2008-2011. The sample in this study determined based on purposive sampling. Data used in this study is a secondary data such as annual reports or financial reports. The results from this study are (1) bankruptcy prediction model having no significant impact on obtaining a going concern audit opinion, (2) leverage having a significant impact on obtaining a going concern audit opinion, (3) audit lag leverage having a significant impact on obtaining a going concern audit opinion, (4) company size having no significant impact on obtaining a going concern audit opinion. Keywords: obtaining a going concern audit opinion, bankruptcy prediction model,leverage, audit lag, company size